Achieving High Specific Capacity through a Two-Electron Reaction in Hypothetical Li2VFSiO4: A First-Principles Investigation. Issue 6 (1st January 2015) - Li, Yunsong; Huang, Baoling; Cheng, Xuan; Zhang, Ying
Abstract : First-principles calculations have been conducted to investigate the feasibility of full extraction of two Li ions in transition metal silicates through a fluorine substitution. The structural, electronic, and electrochemical properties as well as the delithiation mechanisms of both Li2 VOSiO4 and its isostructural derivative, hypothetical Li2 VFSiO4, are explored. The calculated results indicate that the delithiation mechanisms of Li2 VOSiO4 are significantly modified by F − substitution for O 2− due to their different valance states. The first and second Li ion extractions are associated with the V 4+ /V 5+ and O 2− /O ɤ − (1 < ɤ < 2) redox couples for Li2 VOSiO4, and the V 3+ /V 4+ and V 4+ /V 5+ redox couples for Li2 VFSiO4, respectively. The difference between the redox reactions in the two compounds is the major reason for the drop of the second Li delithiation voltage from 5.12 V for Li2 VOSiO4 to 3.7 V for hypothetical Li2 VFSiO4, which is well in the stable range of the conventional commercial electrolytes. A high theoretical specific capacity (above 300 mAh g −1 ) may be achieved in Li2 VFSiO4 with appropriate delithiation voltages (ca. 3.5–3.7 V) and a small volume variation (ca. 1.0%).